Energieprognose mittels Methods-Energy Measurement: Berücksichtigung des Energiebedarfs in der frühen Planungsphase durch komponentenbasierte Energieplanung - Bornschlegl, Martin; Bregulla, Markus; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2015)
The reduction of energy costs of manufacturing technologies is both an important and current objective for factory operators. To achieve an estimation of the energy consumption in an early planning stage, a suitable forecast approach is required. This article shows how the prospective energy consumption can be determined by using Methods-Energy Measurement. This method contributes to identify and realize sustainable solutions in advance and as a result, increases the profitability of a factory.
CRIS-Team Scopus Importer:2023-03-07